Long-term outcomes after ABO-incompatible kidney transplantation; a single-center French study - Zhiyar Abdulrahman; Hamza Bennani Naciri; Asma Allal; Federico Sallusto; Bénédicte Debiol; Laure Esposito; Céline Guilbeau-Frugier; Nassim Kamar; Lionel Rostaing (Society of Diabetic Nephropathy Prevention, 2017)
Background: ABO-incompatible (ABOi) is as efficient as ABO-compatible (ABOc) kidneytransplantation in the setting of live-donation. Objectives: To evaluate the long-term outcomes (i.e. >6 months) of 44 consecutive ABOi living-donor kidney-transplants (KTx). The results were compared to those from 44 ABOc KTx that were matched with ABOi-patients on age, gender, and date of transplantation. Patients and Methods: With regards to immunosuppression (IS) only ABOi-patients received pre-transplant IS, that included rituximab. Induction therapy relied significantly more frequently on basiliximab in ABOc- than in ABOi-patients 77.2% vs. 38.6% (P = 0.0002). Post-transplant IS relied only on tacrolimus/mycophenolic acid and steroids in ABOipatients, whereas some ABOc-patients were alternatively on cyclosporine (13.6%)/everolimus (11.3%) and no steroids (7%), respectively (P = 0.05). Results: In ABOi-patients there was no isoagglutinin titer rebound posttransplant. At last follow-up patient and graft survival was similar in the two groups, as well as kidneyallograft function. Acute rejection rates (cellular, humoral, or mixed) were similar across both groups (ABOi: 22.7%; ABOc: 20.4%). With regards to bacterial and viral infections the only significant difference between the two groups was that at month three there were significantly more BKV viruria in ABOi (25%) vs. 6.8% in ABOc (P = 0.03). De novo donor-specific alloantibody were detected in 13.6% ABOi and 4.5% ABOc patients (ns). Readmission rates in our department for less than two days were more frequent for ABOi conversely readmission rates for more than two days was similar across the groups. Conclusions: ABOi-kidney transplantation after desensitization provides in the long-term same results as those observed in live-donor ABOc-kidney transplantation.